(3cJGH aj GdCOH hGdMceIs
(3ChdgG (B:s
(3bGd HYV GdMceGA(B: (3YdGeI GdYGbd Cf dG jJcda eG dG jWjb, hdG jSYi ajeG dG jOQc s
(3BNQgG (B:s
(3hQHeG aGJ HYV Gdbhe eG WdHhG eY GdJCfj hcGf GdMRoe dh YLdhG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B146 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI O MSjf Ydi eMahX GdNGUI HHZOGO (B(107) s
Keywords: (3GdCOHs